Critical Reflections on De-Radicalisation in Indonesia - Ilyas Mohammed (Otoritas : Jurnal Ilmu Pemerintahan, 2020)
Since 9/11 western and non-western governments have implemented counter-counter terrorism and de-radicalisation programs to “inoculate Muslim populations” and de-radicalise those deemed as radicalised through securitization and “moderate Islam”. The Indonesian government and civil society organizations have attempted to address radicalisation by setting up counter-radicalisation and de-radicalisation programs. This paper will critically reflect on the Indonesian de-radicalisation programs. It will first critically discuss the terms radicalisation and de-radicalisation. Then critically assess the Indonesian de-radicalisation programs. In the final section, the author suggests that Indonesia needs to introduce humanitarian activities to make the de-radicalisation programs more effective and overcome labelling and stigmatization.